Strategic management plan for Silangan Multipurpose Cooperative - Raquid, Nolan R. (School of Management, University of the Philippines Mindanao, 2011)
Cooperatives as economic enterprises and as self-help organizations, play a meaningful role in uplifting the socio-economic conditions of their members and their local communities. Over the years, cooperative enterprises have successfully operated locally owned people-centred businesses while also serving as catalysts for social organization and cohesion. With their concern for their members and communities, they represent a model of economic enterprise that places high regard for democratic and human values and respect for the environment. As the world today faces unstable financial systems, increased insecurity of food supply, growing inequality worldwide, rapid climate change and increased environmental degradation, it is increasingly compelling to consider the model of economic enterprise that cooperatives offer. Credit unions operate in a dynamic business environment that is subject to increased competition, regulation and the vagaries of consumer demand. To facilitate the movement's growth, it is imperative that individual credit unions adopt a strategy that provides a sustainable business platform for the credit union?s future development (ILCU, 2007). Silangan Multipurpose Cooperative, a Savings and Credit Cooperative operating mainly in the Davao City area is not immune from all these factors that is why Strategic Planning is of vital importance. The author utilized the Strategic Planning Model by J.A. Pearce and R.B Robinson as a guide throughout the whole strategy formulation process. Data gathering for the internal analysis was conducted through interview and discussions with key management personnel as well as from the financial and other relative reports of the company. The internet, books and other related literature like annual reports from the Cooperative Development Authority provided the necessary data for the external analysis. However, CDA Data List as of December 2010 is still incomplete/temporary due to Coop re-registration as required under the new Coop Law (R.A 9520). Tools such as the Internal Factor Evaluation Matrix (IFEM), External Factor Evaluation Matrix (EFEM), Swot Matrix and Quantitative Strategic Matrix were used to identify factors and areas of the cooperative where the strategy will focus. The result of the whole process resulted in the proposal of a market development method highlighted by strategic alliances with other members of the cooperative network as well as other service providers in order to yield a better capital build up, secure the financial status of SMPC as well as address issues on people awareness. Specifically, savings and credit cooperatives had been around for awhile already and yet still people do not fully comprehend its concept and the promising benefits they may get. In a market development strategy, while endorsing current product offerings or modifying some, attracting/targeting new sub-markets would increase people awareness, eventually increasing membership and fund generation. This is typically ideal for the moment as several local banks are collapsing and people are looking for alternative financial service institutions to cater to their needs.